High molecular weight β-glucan content: Fluorimetric method: Submitted on behalf of the Analysis Committee of the European Brewery Convention - Hagen, W. (BrewingScience, 2004)
Analytica-EBC contains in section 2 "Barley", section 4 "Malt", section 8 "Wort" and section 9 "Beer" the Fluorimetric Method of High Molecular Weight β-Glucan Content. Several collaborative trials in the last years showed unacceptable reprodubility values (R). The reason was the use of different β-glucan standards and different Calcofluor reagent, both available from Scandinavian Breery Laboratory PLC (Catalogue No SBL R#01 for the first one and Catalogue No SBL R#05 or SBL R#04 for Calcofluor, e-mail: sbl@ajl.dk, website: www.ajl.dk). A further source of deviating results is the dilution. The determination is linear only up to about 300mg7l. Dulution of the final extract affects the result. If the β-glucan content in the final extract exceeds 300 mg/l, a new extraction with smaller amount of barley or malt flour has to be made. In case of malt wort, wort or beer the result is reported only "> 300 mg/l".